The Contact/Non-contact Thimble Haptic device - Choi, Woohyeok; Hur, Sungmoon; Kim, Jaeha; Oh, Yonghwan (2015 IEEE INTERNATIONAL CONFERENCE ON MECHATRONICS (ICM), 2015)
This paper presents a new type of the haptic device that give a physical force feedback by contact with the part of the device. The haptic devices for finger have limitation that is contact on the human finger even in no-reaction condition. Because the part of the device contacts with the human body all time, the user feel the disharmony of sense. For these reasons, the proposed device is designed to be moved from the human finger in non-contact conditions. The mechanism of proposed device is explained, and the prototype device is made and the performance of the device is shown.